2018
DOI: 10.5606/tgkdc.dergisi.2018.15361
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of prosthetic bypass grafting for chronic mesenteric ischemia

Abstract: Bu çalışmada kronik mezenterik iskemi tedavisinde prostetik baypas greftleme işleminin erken ve geç dönem sonuçları analiz edildi.Ça lış ma pla nı: Mart 2009 -Mart 2017 tarihleri arasında ateroskleroza bağlı kronik mezenterik iskemi nedeniyle prostetik baypas greftleme yapılan 22 hasta (15 erkek, 7 kadın; ort. yaş 60±10 yıl; dağılım, 32-78 yıl) çalışmaya dahil edildi. Hastaların demografik ve ameliyat verileri retrospektif olarak incelendi. Bul gu lar:Aterosklerozun en yaygın risk faktörleri hipertansiyon, diy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A previous study has reported there were reliable outcomes when using a prosthetic retrograde bypass. 10) As compared with using prosthetic grafts, there are disadvantages associated with using saphenous vein grafts with regard to perfusion mismatches due to small diameters and the risk of kinking due to structural weakness. 10) However, with these types of situations, it is expected that a selected saphenous vein graft would be more advantageous as compared with a prosthetic graft in terms of avoiding enteric erosions due to contact with intra-abdominal organs and preventing mismatched blood flow between the viscera and lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported there were reliable outcomes when using a prosthetic retrograde bypass. 10) As compared with using prosthetic grafts, there are disadvantages associated with using saphenous vein grafts with regard to perfusion mismatches due to small diameters and the risk of kinking due to structural weakness. 10) However, with these types of situations, it is expected that a selected saphenous vein graft would be more advantageous as compared with a prosthetic graft in terms of avoiding enteric erosions due to contact with intra-abdominal organs and preventing mismatched blood flow between the viscera and lower limbs.…”
Section: Discussionmentioning
confidence: 99%